The sensory image in the poetry of Omar bin Aye Rabia - an analytical study (Journal of the College of Basic Education, 2023)
The sensory image in the poetry of Umar ibn Abi Rabi`ah is almost subject. Some scholars say:It is the subject of eating time and drinking it; However, the truth is otherwise; Because Omar's poetry is materialWhenever I read it, the reader finds in it what he did not find in the previous reading, so his poetry has its preamble as wellAbout his pictures that we did not leave the recipient until he looks at them and responds to reading them over and overAs it enchants him with its formulation and drags him into the depth of its experience of the difference in its flowing water, as well asits manipulation of the recipient's feelings before achieving pleasure; Therefore, I wanted to make my own contribution to Omar's diwanEspecially in his sensory images as a mirror of his poetry, reflecting the poet's experiences and adventures, as well asHis sweethearts, who were passionate about him, except for one, and the research revealed those sufferings and experiences that appeared in themThe Hijazi woman has her own opinion, personality, wisdom and sophistication as a human being before she is a femaleI hope that the reader will be satisfied with my description, I worked hard, and it is not for the human being that I soughtThe image as one of the important pillars and technical criteria for straightening poetry "o ((it isRepresentation and measurement of what we know with our minds over what we see with our eyesIt conveys the writer's idea and his passion to his audience, "there is no doubt that it is an expression of the poet's mentality and psychologyBy understanding its dimensions of imagination).Image constituted a major dimension in Arabic poetry as its foundation, especially poetryThe Arab because it is his tool in drawing the embodied imagination with the dimensions of those images that come from the environment of the poetssurrounding them; And that environment is reflected in its similar or studied drawings, extracting feelings that moveDefining the dimensions are complete, filled with the technical prowess represented by the purity of taste and the tenderness of feelings, even